MOTIVASI BELAJAR PADA SISWA BROKEN HOME DI SMP NEGERI 2 KERSAMANAH GARUT - Imas Solihat; Wikanengsih Wikanengsih; Tuti Alawiyah (IKIP Siliwangi, 2019)
The purpose of this study was to determine the learning motivation of broken home students at SMPN 2 Kersamana. The approach used is a qualitative approach with the type of case study research. The subjects in this study were 2 students who experienced a broken home. Techniques in data collection are interviews, observation, and documentation. The results showed that broken home students were not only due to divorce but could also be due to lack of love from their parents, the death of one of our parents, so that it could have an impact on childhood, especially early adolescence, impacting their physical and psychological condition, including the academic development.Keywords: Broken home, Learning Motivation